Biological sampling in the deep sea - Clark, Malcolm R., 1956-; Consalvey, Mireille; Rowden, A. A. (Ashley Alun) (Wiley-Blackwell, 2016)
"The deep sea covers over 60% of the surface of the earth, yet less than 1% has been scientifically investigated. There is growing pressure on deep-sea resources and on researchers to deliver information on biodiversity and the effects of human impacts on deep-sea ecosystems. Although scientific knowledge has increased rapidly in recent decades, there exist large gaps in global sampling coverage of the deep sea, and major efforts continue to be directed into offshore research. Biological Sampling in the Deep Sea represents the first comprehensive compilation of deep-sea sampling methodologies for a range of habitats. It reviews the real life applications of current, and in some instances developing, deep-sea sampling tools and techniques. In creating this book the authors have been able to draw upon the experiences of those at the "coal face" of deep-sea sampling, expanding on the existing methodological texts whilst encompassing a level of technical detail often omitted from journal publications. Ultimately the book will promote international consistency in sampling approaches and data collection, advance the integration of information into global databases, and facilitate improved data analyses and consequently uptake of science results for the management and conservation of the deep-sea environment. The book will appeal to a range of readers, including students, early-career through to seasoned researchers, as well as environmental managers and policy makers wishing to understand how the deep-sea is sampled, the challenges associated with deep survey work, and the type of information that can be obtained"--